Effect of Global Economic Recession on Regional Autonomy Policy South Sumatra 2022 - Chitra Imelda (Universitas Syiah Kuala, 2022)
Law of the Republic of Indonesia Number 9 of 2015 concerning the Second Amendment to Law of the Republic of Indonesia Number 23 of 2014 concerning Regional Government. Regional revenues budgeted in APBD can guarantee that regional and community independence will soon be realized, especially from general allocation funds which will provide certainty for regions in obtaining financing sources. Regarding the effect of the recession on economic growth and government policies, a number of international institutions project world economic growth in 2023 to be in the range of 2.3% -2.9%. In this case, regional income has a relationship with various social physical and economic variables is to identify which variables have an influence on the acceptance of regional income. Through regional autonomy, the transfer of government authority by the central government to autonomous regions aims to achieve prosperity through public services that are basic services as well as leading sector development.